2022
DOI: 10.3390/genes13081379
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Profiling Reveals Potential Candidate Genes, Transcription Factors, and Biosynthetic Pathways for Phosphite Response in Potato (Solanum tuberosum L.)

Abstract: The study was conducted with C31 and C80 genotypes of the potato (Solanum tuberosum L.), which are tolerant and susceptible to phosphite (Phi, H2PO3), respectively. To decipher the molecular mechanisms underlying tolerance and susceptibility to Phi in the potato, RNA sequencing was used to study the global transcriptional patterns of the two genotypes. Media were prepared with 0.25 and 0.50 mM Phi, No-phosphorus (P), and 1.25 mM (phosphate, Pi as control). The values of fragments per kilobase of exon per milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…It is known that plants use different ribosomal proteins for different purposes. For example, the versatile ribosomal protein S3 serves both as a structural and functional element of the ribosome and as a DNA base excision repair enzyme [ 49 , 50 ]. In our current study, the “ribosome” pathway was found to be one of the major KEGG pathways for DEGs in genetic information processing.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that plants use different ribosomal proteins for different purposes. For example, the versatile ribosomal protein S3 serves both as a structural and functional element of the ribosome and as a DNA base excision repair enzyme [ 49 , 50 ]. In our current study, the “ribosome” pathway was found to be one of the major KEGG pathways for DEGs in genetic information processing.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on sweet potato [2] used RNA sequencing to identify transcriptome differences between phosphite-tolerant (Phi) and phosphite-sensitive cultivars. This study revealed differentially expressed genes (DEGs) related to ribosome, plant hormone signal transduction, photosynthesis and plant-pathogen interaction that function differently under Phi stress.…”
mentioning
confidence: 99%